ANALISIS PAJAK, TUNNELING, GROSS MARGIN, DAN KAP SPESIALIS TERHADAP KEPUTUSAN UNTUK MELAKUKAN TRANSFER PRICING - Jumaidi, Lalu Takdir; Bambang, Bambang; Hudaya, Robith (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
The purpose of is to find out the causal relationship from Tax Independent variable, Turnneling, Gross Margin and KAP Specialist toward transfer pricing decision. The result of the statistic analysis shows that only Tax Independent variable influences to transfer pricing decision. Whereas the other variables such as Gross Margin and KAP Specialist are not significantly influencing decision, either partially or simultaneously. This happens because in multinasional automotive industry corporation has a profit increase pattern. The formula of increasing profit company mostey uses managemen evaluation approach and that of increasing management permance uses management strategy approach, such as total quality managenent with ABS, JIT, EOQ, BEP, cost application standard, and Balanceskorecard models, while tax variable influence very much transfer pricing attitude, because the variable deplets very much company profit, on the other hard, the tax price is relatively different from one contry to another and thust, the tax variable influences very much the decesion to perform Trasfer Pricing.